Excellent vibration isolation properties of a curved Euler beam QZS isolator: Simulation and experiment - Xiaoqiang Chong; Zhijing Wu (Advances in Mechanical Engineering)
In this study, a novel curved Euler beam quasi-zero stiffness (CE-QZS) isolator is proposed by limiting the displacement of the curved Euler beam to change its deformation mode, and the excellent vibration isolation properties are presented. The static and dynamic properties and parameter influences are investigated to identify the isolation mechanism of the novel isolator through numerical simulation using the finite element analysis. These studies of the proposed structure show that compared to the curved Euler beam structure, the bearing capacity and quasi-zero stiffness (QZS) range of the CE-QZS isolator have been significantly improved, and the original negative stiffness of the curved Euler beam is eliminated. Moreover, by changing the position of the rails, the position of the QZS range can be altered, allowing for full utilization of the structural space. Furthermore, the bearing capacity, working range, and QZS range of the CE-QZS isolator can be designed by adjusting the spring stiffness and geometric dimensions of the curved Euler beam. The experimental prototype is machined to conduct vibration tests that confirm the accuracy of the simulation analysis and the superiority of the proposed structure.